Risk factors for discontinuation of exclusive breast feeding within 1month: a retrospective cohort study in Japan - Shun Yasuda; Toma Fukuda; Naoya Toba; Norihito Kamo; Karin Imaizumi; Midori Yokochi; Tomoko Okawara; Seiko Takano; Hideko Yoshida; Nobuko Kobayashi; Shingo Kudo; Kyohei Miyazaki; et al. (BMC, 2022)
Abstract Background While breastfeeding provides benefits for infants and the mother, many women either do not breastfeed or terminate breastfeeding earlier than recommended. The aim of this analysis was to identify factors associated with early discontinuation of breastfeeding in Japanese women. Methods This study used data from medical records of women delivering a singleton live birth between March 2017 and August 2019 in Iwase General Hospital, Fukushima Prefecture, Japan to assess cessation of breastfeeding by the 1-month postpartum appointment. Demographic (age at birth, and employment status), medical (parity, and physical and mental condition of the mother; and infant medical factors, such as sex, Apgar score, and jaundice, among other), and family factors (husband/partner, family members living at the same house, among others) in 734 women who had initiated breastfeeding during their delivery hospital stay were examined, and multiple logistic regression was used to determine significant predictors of early cessation of exclusive breastfeeding. Results Bivariate analysis revealed that women who were primipara, unmarried, exposed to secondhand smoke, and employed; those who smoked before pregnancy; and those who had asthma were more likely to discontinue exclusive breastfeeding than other women. Infant factors associated with discontinuation were lower birthweight, earlier gestational age, neonatal intensive care unit admission, treatment for jaundice, or lower weight gain. Multivariable analysis revealed that primiparity, passive smoking before pregnancy, maternal employment, and neonatal jaundice therapy were associated with discontinuation of breastfeeding. Conclusions In particular, women whose partners smoked before pregnancy may need to be targeted for additional support for breastfeeding.